Neuromyelitis Optica Spectrum Disorder Associated with Cryptogenic Organizing Pneumonia in a Young Patient - Shafiq, Irfan; Wahla, Ali Saeed; Uzbeck, Mateen Haider; Khan, Naureen; Zoumot, Zaid (European Journal of Case Reports in Internal Medicine, 2022)
Neuromyelitis optica spectrum disorder (NMOSD) is associated with other autoimmune disorders and probably with cryptogenic organizing pneumonia (COP) as well. Here we present the case of a 14-year-old girl presenting with typical NMOSD together with radiological evidence of COP. Our case is unique as the previous two reports of this association were in elderly patients.